2020
DOI: 10.21203/rs.3.rs-16248/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surveillance of genetic markers associated with Plasmodium falciparum resistance to artemisinin-based combination therapy in Pakistan, 2018-2019

Abstract: Background: The spread of artemisinin resistance in the Greater Mekong Subregion of Southeast Asia poses a significant threat for current anti-malarial treatment guidelines globally. The aim of this study was to assess the current prevalence of molecular markers of drug resistance in Plasmodium falciparum in the four provinces with the highest malaria burden in Pakistan, after introducing artemether-lumefantrine as first line treatment in 2017.Methods: Samples were collected during routine malaria surveillance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similarly, a study conducted in Pakistan in 2013 found the same results 8 . A survey of clinical isolates collected from all over Pakistan in 2018 found that 98.3% of the country had the CQR 15 , and comparable results have been reported from adjacent countries 26 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly, a study conducted in Pakistan in 2013 found the same results 8 . A survey of clinical isolates collected from all over Pakistan in 2018 found that 98.3% of the country had the CQR 15 , and comparable results have been reported from adjacent countries 26 .…”
Section: Discussionmentioning
confidence: 61%
“…Molecular markers of drug resistance against SP have been reported in a few studies on blood samples representing different Pakistan provinces except for the Federally Administered Tribal Area (FATA) in Pakistan 12,13 . In in vitro/in vivo investigations have revealed the artemisinin resistance along the Thailand-Cambodia border, in Vietnam, Myanmar and other Southeast Asian countries 14 but it is still an effective antimalarial drug in Pakistan 12,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study conducted in Pakistan in 2013 found the same results 8 . A survey of clinical isolates collected from all over Pakistan in 2018 found that 98.3% of the country had the CQR 15 , and comparable results have been reported from adjacent countries 26 .…”
Section: Discussionmentioning
confidence: 61%
“…Molecular markers of drug resistance against SP have been reported in a few studies on blood samples representing different Pakistan provinces except for the Federally Administered Tribal Area (FATA) in Pakistan 12,13 . In in vitro/in vivo investigations have revealed the artemisinin resistance along the Thailand-Cambodia border, in Vietnam, Myanmar and other Southeast Asian countries 14 but it is still an effective antimalarial drug in Pakistan 12,15 .…”
Section: Introductionmentioning
confidence: 99%